Two pairs of phenolic enantiomers from the leaves of Eucommia ulmoides Oliver. Issue 8 (18th April 2019) - Yan, Jian-Kun; Shi, Xu-Liu; Donkor, Paul Owusu; Gao, Xiu-Mei; Ding, Li-Qin; Qiu, Feng
Abstract: Two pairs of new phenolic enantiomers, (+)-eucophenolic A (1a ), (-)-eucophenolic B (1b ), (-)-eucophenolic C (2a ), (+)-eucophenolic D (2b ) were isolated from the leaves of Eucommia ulmodies Oliver by chiral enantiomeric resolution. Their structures were elucidated based on extensive spectroscopic analysis. The absolute configurations of1a /1b and2a /2b were determined by empirical method and the calculated ECD and OR. All compounds were tested for Hep G2 tumour cell lines. However, no compounds showed potential cytotoxic activities against Hep G2 in vitro . Abstract :